Plant-level employment development before collective displacements: comparing mass layoffs, plant closures and bankruptcies - Daniel Fackler; Steffen Müller; Jens Stegmaier (Applied Economics, 2018)
This article analyzes the development of employment levels and worker flows before bankruptcies, plant closure without bankruptcies and mass layoffs. Utilizing administrative plant-level data for Germany, we find no systematic employment reductions prior to mass layoffs, a strong and long-lasting reduction prior to closures, and a much shorter shadow of death preceding bankruptcies. Employment reductions in closing plants, in contrast to bankruptcies and mass layoffs, do not come along with increased worker flows. These patterns point to an intended and controlled shrinking strategy for closures without bankruptcy and to an unintended collapse for bankruptcies and mass layoffs.
Keywords: L2; D22; J65; 330; Job displacement; shadow of death; plant disclosure; bankruptcy; mass layoff